Al2O3 adsorbent for defluorination of zinc sulfate solution as well as preparation and application of Al2O3 adsorbent

The hydrothermal method is used to prepare porous Al2O3 adsorbent with high specific surface area and high pore size, which solves the problems of low adsorption capacity and large usage in the prior art, and achieves efficient defluorination of zinc sulfate solution and reduces production costs.

CN119406369APending Publication Date: 2025-02-11XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411744143.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing aluminum-based adsorbents have low defluorination efficiency in zinc sulfate solution and insufficient adsorption capacity, resulting in large usage, high cost, and complex modification processes.

Method used

Hydrothermal method is used to prepare porous Al2O3 adsorbents with high specific surface area and high pore size. By controlling the molar ratio of aluminum salt, precipitant and dispersant, the adsorption performance is significantly improved and the modification process is eliminated.

Benefits of technology

The adsorption capacity of fluoride ions in zinc sulfate solution is significantly improved, with an adsorption capacity of about 12 mg/g, which is much higher than that of traditional adsorbents, reducing the usage and production costs, and improving the defluorination efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406369A_ABST
    Figure CN119406369A_ABST
Patent Text Reader

Abstract

The invention discloses an Al2O3 adsorbent for defluorination of a zinc sulfate solution as well as preparation and application of the Al2O3 adsorbent. The preparation method comprises the following steps: stirring and mixing a precipitator, a water-soluble aluminum salt and a dispersing agent; heating the mixture, and continuously crystallizing to obtain a precipitate; c, washing, centrifuging, drying and grinding for multiple times to obtain a precursor; and roasting the precursor to generate the Al2O adsorbent for defluorination of a white zinc sulfate solution. The adsorbent has good adsorption performance and excellent surface area, pore size distribution and porosity. The adsorbent has the advantages of high specific surface area, high aperture, capability of improving F <-> curing, good adsorption selectivity and high adsorption capacity, and can effectively reduce the fluorine ion content in an industrial zinc sulfate solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of purification and defluorination of zinc sulfate solution in the process of zinc hydrometallurgy, and particularly relates to a preparation method and application of an Al2O3 adsorbent for defluorination of zinc sulfate solution. Background Art

[0002] Zinc is an indispensable light gray transition metal in modern life and is widely used. Modern zinc refining processes are mainly divided into two categories: pyrometallurgical zinc smelting process and hydrometallurgical zinc smelting process. Among them, the hydrometallurgical zinc smelting process (roasting-leaching-purification-electrodeposition) accounts for about 85% of the world's total zinc production. This process has the advantages of good comprehensive resource utilization, low energy consumption, and environmental friendliness. However, with the development and utilization of mineral resources, high-grade zinc ore concentrates are constantly decreasing, the raw material composition of zinc smelting is becoming more and more complex, and the proportion of high-fluorine impurities in the raw materials is increasing year by year. As a result, F in ZnSO4 solution - The concentration inevitably increases, corroding the cathode and anode during the electrolytic process, causing the Zn in the electrolyte to 2+ Direct discharge to the aluminum surface and forming a solid solution with aluminum causes difficulty in zinc stripping and reduces cathode current efficiency. This not only shortens the service life of the anode plate, but also affects the grade rate of zinc ingots, deteriorates the working environment, and endangers the health of workers. The hydrometallurgical zinc industry generally requires that the F in the ZnSO4 solution be - The concentration was controlled at 50 mg·L -1 Below. At present, the main methods for defluorination of ZnSO4 solution are chemical precipitation, flocculation precipitation, extraction, ion exchange and adsorption. Most processes have high costs or long defluorination times. The adsorption method is the most promising defluoridation agent due to its advantages of low cost, simple operation, strong defluorination ability and no secondary pollution, especially aluminum-based materials. However, for the defluorination of zinc sulfate solution in the wet zinc smelting system, the occurrence state of fluoride ions is complex, and the defluorination efficiency of activated alumina alone is extremely limited. The low adsorption capacity (<10 mg / g) limits their application, and the affinity for fluorine can be increased by modification.

[0003] The main modification methods in existing research include manganese modification, calcium-magnesium modification, iron modification, rare earth element modification, acid modification, etc., but the process is complicated and the cost is high. Studies have shown that alumina-based adsorbents have a defluorination effect in zinc sulfate solution. For example, the adsorption amount of modified aluminum hydroxide in a simulated zinc sulfate solution reached 3.68 mg / g. Al2O3-MgO nanosheets with a layered porous structure were prepared by hydrothermal roasting. When the dosage was greater than 10 g / L, the fluoride ion content dropped to below 50 mg / L, and the adsorption amount was 9.13 mg / g. For industrial applications, the amount of adsorbent should be kept at a lower level (or the adsorption capacity should be further increased) to ensure effective control of costs during use.

[0004] In summary, the current aluminum-based adsorbents used in the defluorination of zinc sulfate solutions have problems such as low adsorption capacity, large amount of adsorbent used, poor selectivity, or the need to introduce other metal cations into alumina, and it is difficult to improve the performance of the adsorbent again after its preparation. These problems make practical applications difficult and the production costs of enterprises are too high. Summary of the invention

[0005] In order to solve the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a preparation method and application of an Al2O3 adsorbent for defluorination of zinc sulfate solution, so as to solve the technical problems in the prior art due to the complex preparation process, the need to dope alumina with other metal cations to introduce new metal elements and low defluorination efficiency, and to provide a porous Al2O3 adsorbent for defluorination of zinc sulfate solution with high specific surface area and high pore size.

[0006] The present invention is achieved through the following technical solutions.

[0007] One aspect of the present invention provides a method for preparing an Al2O3 adsorbent for defluorination of zinc sulfate solution, comprising the following steps:

[0008] a. Mix the precipitant, water-soluble aluminum salt and dispersant in a molar ratio of (5-40):1:

[0009] (0.02-0.25) was dissolved in 100 parts of deionized water and stirred to obtain a mixed transparent solution A;

[0010] b. After mixing and stirring solution A, transfer it to a polytetrafluoroethylene-lined autoclave, heat it, and continue crystallization to obtain a precipitate;

[0011] c. washing, centrifuging, drying and grinding the precipitate several times to obtain a precursor;

[0012] d. Calcine the precursor to generate a white adsorbent.

[0013] Preferably, the water-soluble aluminum salt is at least one of aluminum nitrate nonahydrate, aluminum sulfate 18hydrate, and aluminum chloride hexahydrate.

[0014] Preferably, the precipitant is prepared by mixing an inorganic precipitant A and an organic precipitant B in a molar ratio of 0 to 4:1 to 6;

[0015] The inorganic precipitant A comprises at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonia water, ammonium carbonate or ammonium bicarbonate;

[0016] The organic precipitant B includes at least one of urea, sodium citrate or oxalic acid.

[0017] Preferably, the dispersant includes at least one of citric acid, propylene glycol, polyethylene glycol, dodecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, and sodium hexadecylbenzene sulfonate.

[0018] Preferably, in step a, the raw materials are mixed in a magnetic water bath at 25-65° C. and stirred at a speed of 80-150 r / min for 30-120 min.

[0019] Preferably, in step b, solution A is heated to 120-180° C. in an oven and crystallization is continued for 10-24 hours.

[0020] Preferably, in step c, the centrifugal washing is performed at a rotation speed of 5000-7000 r / min for 5-10 min, and repeated 3-10 times; and the drying temperature is 80-100°C.

[0021] Preferably, in step d, the precursor is calcined at 350-650° C. for 120-480 min to generate a white adsorbent.

[0022] Another aspect of the present invention provides an Al2O3 adsorbent for defluorination of zinc sulfate solution prepared by the method.

[0023] The present invention adopts the above technical solution, which has the following beneficial effects:

[0024] (1) The present invention uses inorganic aluminum salt as aluminum source raw material, adds precipitant and dispersant, and the dispersant acts as a structure-directing agent to control the crystal structure of the material and significantly improve the adsorption performance of the material; a hydrothermal method is used to construct a new type of efficient, cheap, and eco-friendly defluorination agent, which eliminates the modification process and is a novel defluorination agent for F in ZnSO4 solution. - Removal opens up a new avenue.

[0025] (2) The Al2O3 adsorbent for defluorination of zinc sulfate solution prepared by the hydrothermal synthesis technology of the present invention is an amorphous nano material, and the crystals are distributed in the shape of rice grains.

[0026] (3) The Al2O3 adsorbent for defluorination of zinc sulfate solution of the present invention has a high specific surface area and a high pore size, which can improve the solidification of F - It has good adsorption selectivity and high adsorption capacity. The adsorption capacity is about 12 mg / g, which is 1.5 to 5 times the adsorption capacity of existing adsorbents.

[0027] The Al2O3 adsorbent for defluorination of zinc sulfate solution prepared by the invention can be used in the adsorption of industrial zinc sulfate solution and the defluorination of fluorine-containing solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:

[0029] Figure 1 The SEM image of the defluorinating agent preferably prepared in the present invention;

[0030] Figure 2 The XRD diagram of the defluorinating agent preferably prepared in the present invention. DETAILED DESCRIPTION

[0031] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0032] The embodiment of the present invention provides a method for preparing an Al2O3 adsorbent for defluorination of a zinc sulfate solution, comprising the following steps:

[0033] Step 1: Precipitant: water-soluble aluminum salt [Al 3+ ]: The dispersant is dissolved in 100 mL of deionized water at a molar ratio of (5-40):1:(0.02-0.25). The raw materials are mixed in a magnetic water bath at 25-65°C and stirred at a speed of 80-150 r / min for 30-120 min. The obtained mixed transparent solution is recorded as solution A.

[0034] As a preferred embodiment, anionic surfactant is used as dispersant according to the dispersant: [Al 3+ ] is dissolved in deionized water at a molar ratio of 1:4 to 14.

[0035] The precipitant is composed of an inorganic precipitant A and an organic precipitant B in a molar ratio of 0-4:1-6, the inorganic precipitant A is at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonia water, ammonium carbonate or ammonium bicarbonate, and the organic precipitant B is at least one of urea, sodium citrate or oxalic acid.

[0036] The water-soluble aluminum salt is at least one of soluble aluminum salts such as aluminum nitrate nonahydrate, aluminum sulfate 18hydrate, and aluminum chloride hexahydrate.

[0037] Wherein, the dispersant is at least one of citric acid, propylene glycol, polyethylene glycol, dodecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, and sodium hexadecylbenzene sulfonate.

[0038] Step 2: After mixing and stirring the solution A obtained in step 1, transfer it to a polytetrafluoroethylene-lined autoclave, and heat it in an oven to 120-180° C. for continuous crystallization for 9-24 hours. As a preferred embodiment, heat it in an oven to 130-170° C. for continuous crystallization for 10-20 hours.

[0039] Step 3: After the reaction in step 2 is completed, the precipitate in the reaction kettle of step 2 is washed several times, centrifuged at a speed of 5000-7000 r / min for 5-10 minutes, and repeated 3-10 times; the white precipitate is dried and ground at a drying temperature of 80-100° C. to obtain a precursor.

[0040] Step 4: calcine the precursor at 350-650° C. for 120-480 min to generate a white adsorbent.

[0041] The calcination reaction atmosphere is any atmosphere, preferably calcined at 370-520°C for 120-400 min. The calcination under temperature conditions heats the precursor to decompose and transform it, thereby obtaining the target product. This process usually involves thermal decomposition of the precursor and possible gas-solid reaction, and finally obtains nano-Al2O3 powder.

[0042] Adsorption experiment:

[0043] The obtained adsorbent is added into industrial zinc sulfate solution at a liquid-solid ratio of 2-10 g / L, and an adsorption experiment is carried out in an oscillator at 25-80° C. The adsorption reaction time is 30-120 min and the oscillation frequency is 80-180 r / min.

[0044] The adsorbent prepared by the present invention is an amorphous aluminum oxide nanomaterial with a surface area of ​​63 to 293 m 2 / g, pore size distribution is 1.5~30.5nm, porosity is 0.15~0.41cm 3 / g. The present invention can effectively reduce the fluoride ion content in the zinc sulfate solution.

[0045] The present invention is further described below through different embodiments.

[0046] Example 1

[0047] 1) Mix the precipitant (sodium hydroxide and urea in a molar ratio of 4:3): water-soluble aluminum salt [Al 3+ Aluminum nitrate nonahydrate: dispersant citric acid were dissolved in 100 mL of deionized water at a molar ratio of 20:1:0.2, and stirred at 150 r / min for 30 min at 35°C. The mixed transparent solution obtained after sufficient stirring was recorded as solution A.

[0048] 2) The solution A obtained in step 1) was mixed, stirred, and then transferred to a 250 mL high-pressure reactor lined with polytetrafluoroethylene, and heated to 160° C. in an oven for continuous crystallization for 12 h to obtain a white precursor.

[0049] 3) After the reaction in step 2) is completed, the white precipitate is dried and ground to obtain a precursor; the precursor is treated in a centrifuge at a speed of 5000 r / min for 10 min, repeated 8 times to remove residual urea, and dried in an oven at 80°C.

[0050] 4) The precursor dried in step 3) is calcined at 600° C. for 120 min to generate a white adsorbent.

[0051] The surface area of ​​the adsorbent prepared in this example is 293m 2 / g, pore size distribution is 20.5nm, and porosity is 0.35cm 3 / g.

[0052] 5) The adsorbent obtained in step 4) is added to an industrial zinc sulfate solution. The adsorbent is added to the industrial zinc sulfate solution (fluorine content is 127.36 mg / L, pH is 5.4) at a liquid-to-solid ratio of 10 g / L. An adsorption experiment is performed in an oscillator with an oscillation frequency of 150 rad / min, an adsorption time of 60 min, and an adsorption temperature of 30° C. After adsorption, the fluorine ion concentration of the solution drops to 19.45 mg / L, and the adsorption capacity of the adsorbent is 10.791 mg / g.

[0053] Example 2

[0054] 1) Mix the precipitant (sodium carbonate and sodium citrate in a molar ratio of 2:1): water-soluble aluminum salt [Al 3+ Aluminum sulfate 18hydrate: dispersant propylene glycol were dissolved in 100 mL of deionized water at a molar ratio of 30:1:0.1, and stirred at 120 r / min for 60 min at 25°C. The mixed transparent solution obtained after sufficient stirring was recorded as solution A;

[0055] 2) The solution A obtained in step 1) was mixed, stirred, and then transferred to a 250 mL high-pressure reactor lined with polytetrafluoroethylene, and heated to 180° C. in an oven for continuous crystallization for 10 h to obtain a white precursor.

[0056] 3) After the reaction in step 2) is completed, the white precipitate is dried and ground to obtain a precursor; the precursor is treated in a centrifuge at a speed of 6000 r / min for 8 minutes, repeated 5 times to remove residual urea, and dried in an oven at 100°C.

[0057] 4) The precursor dried in step 3) was calcined at 350° C. for 480 min to generate a white adsorbent.

[0058] The surface area of ​​the adsorbent prepared in this example is 251m 2 / g, pore size distribution is 10.5nm, and porosity is 0.41cm 3 / g.

[0059] 5) The adsorbent obtained in step 4) is added to an industrial zinc sulfate solution. The adsorbent is added to the industrial zinc sulfate solution (fluorine content is 127.36 mg / L, pH is 5.4) at a liquid-to-solid ratio of 2 g / L. An adsorption experiment is performed in an oscillator with an oscillation frequency of 80 rad / min, an adsorption time of 120 min, and an adsorption temperature of 25° C. After adsorption, the fluorine ion concentration of the solution drops to 45.42 mg / L, and the adsorption capacity of the adsorbent is 8.194 mg / g.

[0060] Example 3

[0061] 1) Mix the precipitant (ammonia water and sodium citrate in a molar ratio of 3:5): water-soluble aluminum salt [Al 3+ Aluminum chloride hexahydrate: dispersant polyethylene glycol was dissolved in 100 mL of deionized water at a molar ratio of 40:1:0.18, and stirred at 80 r / min for 120 min at 50°C. The mixed transparent solution obtained after sufficient stirring was recorded as solution A;

[0062] 2) The solution A obtained in step 1) was mixed, stirred, and then transferred to a 250 mL high-pressure reactor lined with polytetrafluoroethylene, and heated to 130° C. in an oven for continuous crystallization for 20 h to obtain a white precursor.

[0063] 3) After the reaction in step 2) is completed, the white precipitate is dried and ground to obtain a precursor; the precursor is treated in a centrifuge at a speed of 7000 r / min for 5 minutes, repeated 3 times to remove residual urea, and dried in an oven at 90°C.

[0064] 4) The precursor dried in step 3) was calcined at 550° C. for 360 min to generate a white adsorbent.

[0065] The surface area of ​​the adsorbent prepared in this example is 186 m 2 / g, pore size distribution is 15.8nm, and porosity is 0.27cm 3 / g.

[0066] 5) The adsorbent obtained in step 4) is added to an industrial zinc sulfate solution. The adsorbent is added to the industrial zinc sulfate solution (fluorine content is 127.36 mg / L, pH is 5.4) at a liquid-to-solid ratio of 3 g / L. An adsorption experiment is performed in an oscillator with an oscillation frequency of 100 rad / min, an adsorption time of 60 min, and an adsorption temperature of 40° C. After adsorption, the fluorine ion concentration of the solution drops to 42.34 mg / L, and the adsorption capacity of the adsorbent is 8.502 mg / g.

[0067] Example 4

[0068] 1) Mix the precipitant (ammonium carbonate and oxalic acid in a molar ratio of 1:6): water-soluble aluminum salt [Al 3+] Aluminum chloride hexahydrate: dispersant dodecyltrimethylammonium bromide + sodium dodecylbenzenesulfonate were dissolved in 100 mL of deionized water at a molar ratio of 5:1:0.25, and stirred at 100 r / min for 80 min at 45°C. The mixed transparent solution obtained after sufficient stirring was recorded as solution A;

[0069] 2) The solution A obtained in step 1) was mixed, stirred, and then transferred to a 250 mL high-pressure reactor lined with polytetrafluoroethylene, and heated to 170° C. in an oven for continuous crystallization for 9 h to obtain a white precursor.

[0070] 3) After the reaction of step 2) is completed, the white precipitate is dried and ground to obtain a precursor; the precursor is treated in a centrifuge at a speed of 5500 r / min for 7 minutes, repeated 10 times to remove residual urea, and dried in an oven at 90°C.

[0071] 4) The precursor dried in step 3) is calcined at 650° C. for 180 min to generate a white adsorbent.

[0072] The surface area of ​​the adsorbent prepared in this example is 265m 2 / g, pore size distribution is 21.9nm, and porosity is 0.28cm 3 / g.

[0073] 5) The adsorbent obtained in step 4) is added to an industrial zinc sulfate solution. The adsorbent is added to the industrial zinc sulfate solution (fluorine content is 127.36 mg / L, pH is 5.4) at a liquid-to-solid ratio of 5 g / L. An adsorption experiment is performed in an oscillator with an oscillation frequency of 150 rad / min, an adsorption time of 90 min, and an adsorption temperature of 60° C. After adsorption, the fluorine ion concentration of the solution drops to 52.8 mg / L, and the adsorption capacity of the adsorbent is 7.456 mg / g.

[0074] Example 5

[0075] 1) The precipitant ammonium bicarbonate: water-soluble aluminum salt [Al 3+ Aluminum nitrate nonahydrate: dispersant sodium hexadecylbenzenesulfonate were dissolved in 100 mL of deionized water at a molar ratio of 15:1:0.02, and stirred at 65°C at a speed of 150 r / min for 100 min. The mixed transparent solution obtained after sufficient stirring was recorded as solution A;

[0076] 2) The solution A obtained in step 1) was mixed, stirred, and then transferred to a 250 mL high-pressure reactor lined with polytetrafluoroethylene, and heated to 140° C. in an oven for continuous crystallization for 10 h to obtain a white precursor.

[0077] 3) After the reaction in step 2) is completed, the white precipitate is dried and ground to obtain a precursor; the precursor is treated in a centrifuge at a speed of 6500 r / min for 6 minutes, repeated 6 times to remove residual urea, and dried in an oven at 95°C.

[0078] 4) The precursor dried in step 3) is calcined at 400° C. for 420 min to generate a white adsorbent.

[0079] The surface area of ​​the adsorbent prepared in this example is 223m 2 / g, pore size distribution is 29.5nm, and porosity is 0.37cm 3 / g.

[0080] 5) The adsorbent obtained in step 4) is added to an industrial zinc sulfate solution. The adsorbent is added to the industrial zinc sulfate solution (fluorine content is 127.36 mg / L, pH is 5.4) at a liquid-to-solid ratio of 8 g / L. An adsorption experiment is performed in an oscillator with an oscillation frequency of 180 rad / min, an adsorption time of 30 min, and an adsorption temperature of 80° C. After adsorption, the fluorine ion concentration of the solution drops to 60.34 mg / L, and the adsorption capacity of the adsorbent is 6.702 mg / g.

[0081] It can be seen from the above examples that the Al2O3 adsorbent for defluorination of zinc sulfate solution prepared by the present invention solves the technical problems of low adsorption capacity, large amount of adsorbent used, poor selectivity, or the need to introduce other metal cations into alumina, and excessive production cost when used for defluorination of zinc sulfate solution. After adsorption, the fluorine ion concentration of the solution is reduced to 19.45 mg / L at the lowest, and the adsorption capacity of the adsorbent is up to 10.791 mg / g at the highest. It has good adsorption performance and is suitable for adsorption of Al2O3 adsorbent in zinc sulfate solution and defluorination of fluorine-containing solution.

[0082] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.

Claims

1. A method for preparing an Al2O3 adsorbent for defluorination of zinc sulfate solution, characterized in that: The steps include: a. Mix the precipitant, water-soluble aluminum salt and dispersant in a molar ratio of (5-40):1: (0.02-0.25) was dissolved in 100 parts of deionized water and stirred to obtain a mixed transparent solution A; b. heating solution A and continuing crystallization to obtain a precipitate; c. washing, centrifuging, drying and grinding the precipitate several times to obtain a precursor; d. The precursor is calcined to generate a white zinc sulfate solution as an Al2O adsorbent for defluorination.

2. The method for preparing the Al2O3 adsorbent for defluorination of zinc sulfate solution according to claim 1, characterized in that: The water-soluble aluminum salt is at least one of aluminum nitrate nonahydrate, aluminum sulfate 18hydrate, and aluminum chloride hexahydrate.

3. The method for preparing the Al2O3 adsorbent for defluorination of zinc sulfate solution according to claim 1, characterized in that: The precipitant is prepared by mixing an inorganic precipitant A and an organic precipitant B in a molar ratio of 0-4:1-6; The inorganic precipitant A comprises at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonia water, ammonium carbonate or ammonium bicarbonate; The organic precipitant B includes at least one of urea, sodium citrate or oxalic acid.

4. The method for preparing the Al2O3 adsorbent for defluorination of zinc sulfate solution according to claim 1, characterized in that: The dispersant includes at least one of citric acid, propylene glycol, polyethylene glycol, dodecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, and sodium hexadecylbenzene sulfonate.

5. The method for preparing the Al2O3 adsorbent for defluorination of zinc sulfate solution according to claim 1, characterized in that: In step a, the raw materials are mixed in a magnetic water bath at 25-65° C. and stirred at a speed of 80-150 r / min for 30-120 min.

6. The method for preparing the Al2O3 adsorbent for defluorination of zinc sulfate solution according to claim 1, characterized in that: In step b, solution A is heated to 120-180° C. in an oven and crystallization is continued for 10-24 hours.

7. The method for preparing the Al2O3 adsorbent for defluorination of zinc sulfate solution according to claim 1, characterized in that: In step c, centrifugal washing is performed at a rotation speed of 5000-7000 r / min for 5-10 minutes, and repeated 3-10 times; the drying temperature is 80-100°C.

8. The method for preparing the Al2O3 adsorbent for defluorination of zinc sulfate solution according to claim 1, characterized in that: In step d, the precursor is calcined at 350-650° C. for 120-480 min to generate a white adsorbent.

9. An Al2O3 adsorbent for defluorination of zinc sulfate solution prepared by the method according to any one of claims 1 to 8.

10. Use of the Al2O3 adsorbent for defluorination of zinc sulfate solution as claimed in claim 9 in adsorption in zinc sulfate solution and defluorination of fluorine-containing solution.